The hit & turn tennis test: An acoustically controlled endurance test for tennis players - Ferrauti, A.; Kinner, V.; Fernandez-Fernandez, J. (Journal of Sports Sciences, 2011)
This study was conducted to validate and evaluate the "Hit & Turn Tennis Test", an acoustically progressive on-court endurance test for tennis players. Ninety-eight competitive tennis players (53 males, 45 females) of different age groups participated in the study. For validation, the adult male players completed three Hit & Turn tests, one on a clay court and two on a carpet surface, a tennis-specific ball machine test and an incremental treadmill run in a randomized order. A stronger correlation between maximal performance (r = 0.81, P < 0.01) and maximal oxygen uptake (r = 0.96, P < 0.01) was observed between the Hit & Turn test and the ball machine test, than between the Hit & Turn test and the treadmill test. For test-retest, we found a significant correlation between maximal performance on the same (r = 0.83, P < 0.01) and on different surfaces (r = 0.74, P < 0.01). During test evaluation, maximal performance was higher in males than in females (P < 0.01) and increased by consecutive age group in boys (P < 0.01) but not in girls (P = 0.97). In conclusion, Hit & Turn maximum test performance can be recommended as a valid and reliable indicator for tennis-specific endurance.